Unusual melanoma of the scalp with blue nevus-like features and local metastasis: A case report. (April 2019) - George, Sheenagh JK; Green, Peter; Walsh, Noreen MG
We present an unusual case of melanoma in a 76-year-old female covering approximately 80% of her scalp. Partial sampling of the lesion revealed focal blue nevus-like features at the microscopic level. We discuss issues related to blue nevus-like melanomas and highlight the unique clinical presentation of the current case.